Children with screening-detected coeliac disease show increased levels of nitric oxide products in urine - Högberg, L; Webb, C; Fälth-Magnusson, K; Forslund, T; Magnusson, K-E; Danielsson, L; Ivarsson, A; Sandström, O; Sundqvist, T (Acta Paediatrica, 2011)
Aim:  Increased concentration of nitric oxide (NO) metabolites, nitrite and nitrate, in the urine is a strong indication of ongoing small intestinal inflammation, which is a hallmark of the enteropathy of coeliac disease (CD). It has previously been shown that children with symptomatic, untreated CD have increased levels of NO oxidation products in their urine. The aim of this study was to investigate whether screening‐detected, asymptomatic coeliac children display the same urinary nitrite/nitrate pattern. Methods:  In a multicenter screening study, serum samples were collected from 7208 12‐year‐old children without previously diagnosed CD. Sera were analysed for anti‐human tissue transglutaminase (tTG) of isotype IgA. Small bowel biopsy was performed in antibody‐positive children, yielding 153 new cases of CD. In the screening‐detected individuals, the sum of nitrite and nitrate concentrations in the urine was analysed and used as an indicator of NO production. For comparison, 73 children with untreated, symptomatic CD were studied. Results:  The nitrite/nitrate levels in children with screening‐detected CD and those with untreated symptomatic CD did not differ significantly. Both groups had significantly increased urinary nitrite/nitrate concentrations compared to the children with normal small bowel biopsy (p < 0.001). Conclusion:  Children with screening‐detected CD have increased production of NO just as children with untreated symptomatic CD. High NO metabolite levels in the urine may indicate a pathogenetic feature of CD and be a marker of major clinical importance.